The chamber cantatas of Antonio Vivaldi - Talbot, Michael 1943- (Boydell & Brewer, 2006)
Detailed survey of Vivaldi's unjustly neglected chamber cantatas, showing them to stand comparison with his more famous works. Vivaldi's chamber cantatas for solo voice, some forty in total, are steadily gaining in popularity: but because of their relatively small place in the oeuvre of a composer famed for his productivity, and also on account of the general scholarly neglect of their genre, they are little discussed in the literature. This book comprehensively explores their literary and musical background, their relation to the composer's biography, the chronology of their composition, and their musical qualities. Each cantata is discussed individually, but there is also a broader consideration of aspects concerning them collectively, such as performance practice, topical allusion, and the conventions of Italian verse. The author argues that while Vivalid's cantatas are not as innovative as his concertos and operas, he produced several masterpieces in the genre that rank with his best music. MICHAEL TALBOT is Emeritus Professor of Music at the University of Liverpool